Blue ocean strategy - Kim, W. Chan (Harvard Business Review Press, 2015)
In this perennial bestseller, embraced by organizations and industries worldwide, globally preeminent management thinkers W. Chan Kim and Renée Mauborgne challenge everything you thought you knew about the requirements for strategic success. Recognized as one of the most iconic and impactful strategy books ever written, Blue Ocean Strategy, now updated with fresh content from the authors, argues that cutthroat competition results in nothing but a bloody red ocean of rivals fighting over a shrinking profit pool. Based on a study of 150 strategic moves (spanning more than 100 years across 30 industries), the authors argue that lasting success comes not from battling competitors but from creating “blue oceans”―untapped new market spaces ripe for growth